Outsourcing in companies with custom production: decision criteria - Beal, Cléber; Costa, Carlos Alberto; Reis, Zaida Cristiane dos; Capoani, Matheus (Sistemas & Gestão, 2019)
Most of the outsourcing models include decision criteria that consider the scenario of companies with serial production, as it is verified in the literature. Thus, this paper aims to discuss the criteria for decision making regarding outsourcing by companies with production to order, that is, customized products. In order to do so, a qualitative, exploratory and descriptive study of the multiple case study type was developed, considering three dimensions of analysis: business arrangements, essential skills and the outsourcing environment. The results revealed two perceptions about outsourcing in an on-demand production scenario: one optimistic and the other that considers outsourcing as an alternative to solving immediate problems. The following decision-making criteria regarding outsourcing were emphasized: emphasis on essential competency, value aggregation, solution to momentary problem, transformation from fixed cost to variable and cost reduction. It is concluded that the results approve the adoption of this evaluative proposal for production environments under order, and the defined dimensions and the proposed instrument can be used in similar production environment scenarios.